Understanding sub-national climate governance: Findings from Nepal, Uganda, Vietnam and Zambia - Ian Christoplos; Charles Aben; Bernard Bashaasha; Hari Dhungana; Esbern Friis-Hansen; Mikkel Funder; Nguyen Thi Thanh Huong; Dil Bahadur Khatri; Lily Salloum Lindegaard; Carol Mweemba; Le Duc Ngoan; Imasiku Nyambe; et al. (Danish Institute for International Studies (DIIS), 2016)
The Paris climate agreement established a new framework for global climate governance that is firmly anchored in national plans and commitments. But who is actually going to take the next steps to implement these plans on the ground and what are the incentives and obstacles they face in moving from words to action? Many have pointed to the important role of local governments and other sub-national institutions, not least in developing countries where the task of adapting to climate change is considerable. Yet little is known about the way such sub-national institutions are responding to climate change, and how they interact with the central state and local communities in practice. This report brings together key findings from a collaborative research programme on the politics, actors and emerging agendas within sub-national climate governance in Africa and Asia. Drawing on research in Nepal, Uganda, Vietnam and Zambia, the reports discusses four key themes in climate change adaptation practice, namely: how the global climate change agenda is downscaled in national and sub-national processes, the frequent disconnect between national climate change policies and sub-national practices, how climate change may be shifting the basis for social contracts and state legitimacy, how climate change is emerging as an arena for struggles over authority and resources
Keywords: 300